Dosimetric Evaluation of Incidental Irradiation to the Internal Mammary Chain After Surgery in Breast Cancer Patients - Wang, Wei; Sun, Tao; Meng, Yingtao; Xu, Min; Zhang, Yingjie; Shao, Qian; Song, Yuanfang; Li, Jianbin (Frontiers in Oncology, 2022)
Background and purpose: The low rate of internal mammary node (IMN) recurrence was attributed to the systemic therapy and the internal mammary chain (IMC) coverage by the tangential fields irradiation. This study aimed to evaluate the incidental irradiation dose to the IMC in breast cancer patients after surgery and to estimate the clinical predictive parameters affecting the magnitude of IMC. Materials and methods: A total of 138 patients treated with postmastectomy radiotherapy and 210 patients undergoing radiotherapy after breast-conserving surgery (BCS) in our hospital were retrospectively analysed. The mean dose (Dmean) to the IMC and the first to third intercostal spaces of IMC levels (ICS1–3) were evaluated. We evaluated the IMC coverage according to the the type of surgery and whether the ipsilateral supraclavicular fossa (SCF) inclued in the irradation field. Results: The incidental radiation dose to IMC was 29.69 Gy, and the dose delivered to IMC, ICS1, and ICS2 showed a greater coverage in the modified radical mastectomy (MRM) group when compared to the BCS group (32.85 vs 27.1 Gy, 26.6 vs 12.5 Gy, 34.63 vs 30.42 Gy). The dose delivered to ICS3 showed no difference between the MRM and BCS groups (37.41 vs 36.24 Gy). Further, 131 patients (37.64%) received radiotherapy to the chest wall and ipsilateral SCF. In univariate analysis, both surgery type and SCF irradiation were parameters affecting the Dmean of incidental radiation to the IMC (r=-0.179, P=0.001; r=-0.175, P=0.001). In multivariate analysis, surgery type was the only correlative factor that affected incidental radiation dose to IMC (r=-3.534, P=0.000). Conclusion: The real influencing factor of incidental dose to IMC was the surgery form rather than the accession of SCF irradiation.